(untitled) (Fiep Bulletin - online, 2011)
This research takes as its object of investigation and intervention playfulness and fantasy of real as axis of childhood cultures essential to the education of children. It is being developed in a public school for kindergarten and its objective is to analyze how these aspects are understood and addressed within the partner institution. The methodology adopted is qualitative and is characterized as action research. The team established an initial contract of partnership and cooperation between its components, outlined the problem and seeks to expand the workshops of the theoretical and practical. The field work is conducted at the institution and the data analysis and systematization of the results involve the entire team. The theoretical framework that guides the project is based, especially in the Sociology of Childhood, which treats the child as a social category whose specificity distinguish her from adults. Part also of the assumption that the concept of childhood is influenced by social, cultural and historical, however, the authors in the field believe that there are elements, called cultures of childhood, to mark their own forms of children are and relate to the people with the natural and social world. Partial results indicate qualitative changes in educational practices of the participants, because the study situations and experiences with the issues, allow the questioning of pedagogical models and educational practices that guide pedagogical work in the context of Childhood Education. Permit, too, despite advances in the process of training of those involved in improving educational practice, which has considered, intentionally, interests and needs of children and their rights to participation, expression and communication.